Using Ketapang Seed Oil Biodiesel as an Environmentally Friendly Renewable Alternative Energy to Improve Diesel Motor Performance - Prasutiyon, Hadi; Prayogi, Urip; Felayati, Frengki Mohammad; sugianto, erik; Santosa, Benaya Prasetya (International Journal of Marine Engineering Innovation and Research, 2024)
The needs of society related to the energy crisis require alternative energy that can replace fossil fuels, such as Ketapang seed biodiesel. Preparation of crude oil by maceration method and making biodiesel through esterification and transesterification process. The research will discuss the performance of diesel engines with biodiesel fuel and Ketapang seed biodiesel with the composition of B0, B10, B20, B30. The test uses a rotation variation of 1200 to 2000 RPM and a load of 1000 to 3000. From the test properties and performance test research, it can be seen that they are related to each other. Biodiesel obtained better performance compared to B10, B20, B30. The lowest Specific Fuel Oil Consumption value is found in biodiesel fuel, where based on the average calculation on the maximum Specific Fuel Oil Consumption graph, B0 fuel produces a lower Specific Fuel Oil Consumption value than B10, B20 and B30 fuels with a difference of 33,759 gr/kWh, 49,661 gr/kWh and 113,694 gr/kWh. In this research process, the results of diesel engine performance using Ketapang seed biodiesel proved to be worse than biodiesel.